CONCEPT AND VALIDATION OF A SYSTEM FOR RECORDING VIBROACOUSTIC SIGNALS OF THE KNEE JOINT - Karpiński, Robert; Machrowska, Anna; Maciejewski, Marcin; Jonak, Józef; Krakowski, Przemysław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
Cartilage degeneration is a serious health condition in modern society, leading to problems in mobility and significant reduction in the quality of life of patients of all ages. It is mainly caused by obesity, workload, sports or trauma to the joint. Proper diagnosis is crucial to implement appropriate treatment to stop the further degeneration of the tissue. Usually the assessment is performed by using magnetic resonance. This paper describes the design and application of an alternative measurement system for vibroartography of the knee joint. The use of such device allows for fast, safe, easy and cheap assessment of joint condition, which in turn can lead to proper treatment planning. Similar portable systems can be rapidly deployed and used by entry level medical staff in hospitals, clinics or at patient’s home. The system consists of an orthosis, set of three vibroacoustic sensors, encoder for reading knee position, microcontroller with galvanic barrier and battery power and a computer for data storage and processing. The system is light, simple and portable. Data is recorded in both closed and open kinematic chains. Results show over 90% diagnostic accuracy based on the data obtained in the process of testing this device. In the future, the system will be further miniaturized and completely placed on the orthosis, leading to more portability and diagnostic merit.